Determination of Quercetin in Soursop (Annona muricata Linn.) Leaves 10 ml Liquid Preparation Using UV-Spectroscopic Method - Sudjarwo, Sudjarwo; Khatimah, Siti Husnul; Annuryanti, Febri (Universitas Airlangga, 2022)
Quercetin was a flavonoid compound that was found in Annona muricata L. leaves. The UV Spectrophotometric method was used to determine quercetin from Annona muricata in liquid. The degradation was determined by selectivity, linearity, accuracy, precision, LOD, and LOQ. Selectivity showed that spectra had maximum absorbance at λ 374 nm. Good linearity was shown by y = 0,07368x - 0,01937 (r = 0,9984; p<0,05). The precision of standard quercetin in a concentration of 6,4 ppm showed a relative standard deviation (RSD) of 0,19%. LOD and LOQ of standard quercetin were 0,0240 µg/ml and 0,0801 µg/ml, and the accuracy was 91,867±7,59%. Determination of quercetin in Annona muricata leaf extract showed a concentration of 12,62±3,29% and (263,96 ± 6,69) mg in 10 ml liquid.Keywords: Quercetin, Annona Muricata L, UV Spectrophotometry, Method of Validation